2021
DOI: 10.1155/2021/5952724
|View full text |Cite
|
Sign up to set email alerts
|

Rare Case of Spinal Neurosarcoidosis with Concomitant Epidural Lipomatosis

Abstract: Introduction. Spinal neurosarcoidosis is a rare disease that can manifest as myelopathy, radiculopathy, or cauda equine syndrome. Spinal epidural lipomatosis is also a rare condition resulting from overgrowth of epidural fat tissue causing compressive myelopathy. To our knowledge, there are no reports linking epidural lipomatosis and spinal neurosarcoidosis. Case Report. We describe a case of progressive myelitis in the presence of concomitant spinal neurosarcoidosis and epidural lipomatosis which was a challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…26 One study reported aberrant lipid metabolism to be related to idiopathic SEL. 54 However, these patients were also obese, again highlighting the controversial definition of idiopathic disease. 26 While not an established risk factor, concomitant spinal neurosarcoidosis with SEL has been reported.…”
Section: Spine Surgerymentioning
confidence: 98%
See 1 more Smart Citation
“…26 One study reported aberrant lipid metabolism to be related to idiopathic SEL. 54 However, these patients were also obese, again highlighting the controversial definition of idiopathic disease. 26 While not an established risk factor, concomitant spinal neurosarcoidosis with SEL has been reported.…”
Section: Spine Surgerymentioning
confidence: 98%
“…1,59,60 CONSERVATIVE AND MEDICAL MANAGEMENT Weight reduction should be pursued for obese patients, regardless of underlying etiology, as studies have shown improvement of symptoms irrespective of the cause. 1,54,61 The degree of weight reduction for symptomatic improvement varies from patient to patient, although one study recommended a 15-kilogram reduction to improve SEL-related symptoms. 18 More aggressive weight reduction methods, such as bariatric surgery and calorie-restricted diets, have also been noted to provide clinical improvement due to significant loss of epidural fat deposition.…”
Section: Treatment and Management Introduction And Overviewmentioning
confidence: 99%
“…Other risk factors include exogenous steroid intake and previous spinal surgery [ 30 ]. An association with neurosarcoidosis and inflammatory involvement of the factors TNFα and IL-1β has also been described [ 15 ]. Furthermore, studies have been able to show that depending on the etiology of SEL, different localizations in the spine are affected [ 10 , 17 , 18 , 24 ].…”
Section: Introductionmentioning
confidence: 99%